Temperature and salinity effects on the Raman scattering cross section of the water OH‐stretching vibration band in NaCl aqueous solutions from 0 to 300 °C. (21st September 2016) - Wu, Xiangen; Lu, Wanjun; Ou, Wenjia; Caumon, Marie‐Camille; Dubessy, Jean
Abstract : Water is often used as an internal standard in quantitative Raman spectroscopic measurements of dissolved species in aqueous solutions containing salts at varying temperatures. However, the effects of temperature and dissolved ions on the relative differential Raman scattering cross section (RSCS) of the OH‐stretching vibration band of water at elevated temperatures and salinities are not well defined quantitatively. In this study, the Raman spectra of NaCl solutions with different salinity (from 0 to 5 mol NaCl/kg · H2 O) at 20 °C at atmospheric pressure and from 0 to 300 °C at 30 MPa were studied. The relative RSCS of the OH‐stretching vibration band of liquid water (σ( m NaCl, T, 30 MPa) /σ( Pure water, 20 °C, 30 MPa) ) as a function of temperature ( T, in °C) and salinity ( m NaCl, in mol/kg · H2 O) was established: σ m NaCl, T, 30 M P a / σ ( Pure water, 20 o C, 30 M P a ) = f T, m NaCl = a T − 20 + b where a = 0.000089 × m NaCl 1/2 − 0.001164; b = 0.0355 × m NaCl + 1; The RSCS of the OH‐stretching vibration band of water in pseudo back‐scattering geometry decreases linearly with increasing temperature, but increases with the addition of dissolved NaCl within the whole temperature range. The enhancement factor of the RSCS by dissolved NaCl increases with temperature. Such effects of temperature and salinity should be considered in quantitative Raman spectroscopic study of species concentration in aqueous solution at high temperature when using water as internal standard. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The relative Raman scattering cross section (RSCS) of the OH‐stretching vibration band of liquid water (σ( m NaCl, T, 30 MPa) /σ( Pure water, 20 o C, 30 MPa) ) as a function of temperature ( T, in °C) and salinity ( m NaCl, in mol/kg · H2 O) was established. The relative RSCS of water OH band decreases linearly with increasing temperature and increases with increasing NaCl concentration. The enhancement effect of NaCl increases with rising temperature.